Project management in the construction industry: identifying logistics problems and ways to optimise them - Polusmiak, Yuliia; Pavliuk, Tetiana; Kosach, Ivan (Management and Entrepreneurship: Trends of Development, 2024)
The authors study the process of optimisation of logistics processes in the construction industry through the introduction of modern information technologies. In particular, they focus on the implementation of systems that improve the efficiency of resource management, reduce costs, and ensure the timely implementation of construction projects. The main areas of optimisation include the implementation of a supply chain management (SCM) system, a transport management system (TMS), warehouse accounting using WMS, and the integration of BIM technologies. The construction industry is one of the most complex and multifaceted in the economy, requiring effective management of all stages of the project life cycle - from planning and design to implementation and commissioning. One of the key aspects of successful construction project management is the efficient organisation of logistics processes, including the supply of construction materials, transportation, warehousing and distribution of resources. However, despite the importance of this aspect, logistics in construction remains one of the most problematic and underestimated areas. The article also emphasises the importance of phased implementation of these systems to achieve maximum results. It is determined that a phased approach allows for a gradual increase in logistics efficiency, with specific results at each stage. The introduction of information technology contributes to a significant increase in the competitiveness of companies in the construction sector, reducing costs and ensuring timely project implementation. JEL Classification: Р43, О22, М20